Discovering Associations: Kawasaki Disease and COVID-19 - Nicholas Peterson; Kaustubh Sagdeo; Donna Tyungu; Cristin Harper; Kyle Mihaylo; Elza Pollak-Christian (Case Reports in Pediatrics)
The COVID-19 pandemic has resulted in over 3.6 million confirmed cases and over 254,000 deaths worldwide. It has been theorized that children who are asymptomatic or who do not display significant respiratory symptoms are potential vectors for community transmission of the SARS-CoV-2 virus. This is incompletely understood due to the current lack of widespread testing in the pediatric population. We describe a case of a 2-year-old female who presented with symptoms of prolonged fever, conjunctivitis, extremity edema, rash, dry/cracked lips, fussiness and fatigue, and a notable absence of respiratory symptoms. She was diagnosed with and treated for Kawasaki disease. Due to her prolonged fever, she was tested for COVID-19 which was positive; however, she did not develop respiratory symptoms during her illness. At the time of manuscript submission, this is the second case report to our knowledge showing an association between Kawasaki Disease and SARS-CoV-2 virus, both of which are poorly understood diseases in the pediatric population. This case highlights the value of testing pediatric patients for COVID-19 who present with fever in the absence of other symptoms to improve epidemiologic measures during the ongoing pandemic, and it also adds to a foundation of cases for future research on the presence of a link between Kawasaki Disease and COVID-19.